ANALISIS KECERDASAN INTRAPERSONAL MAHASISWA PADA PROGRAM STUDI PG-PAUD FKIP UNIVERSITAS MUHAMMADIYAH BUTON - rahman saleh (FKIP Universitas sriwijaya, 2018)
The general purpose of this research is to obtain information about intrapersonal intelligence of Student Program of Early Childhood Education FKIP UMB. The method used in this research is descriptive method. Data collection techniques used are indirect communication techniques using questionnaires (questionnaire). Data were analyzed using descriptive statistic percentage. The result of questionnaire analysis about student intrapersonal intelligence can be described as follows: Self-respect, obtained 69.78% with good category; Be polite, obtained good result 74,30%; Not hostile to themselves, obtained a good yield of 76.25%; Be honest, obtained results 79.47% with good category. Based on the findings it can be concluded that: most students can appreciate themselves, almost all students can be polite, not hostile to themselves, and be honest. This shows that they are always optimistic in the face of a failure, and do not regret themselves or even self-blame which can lead to frustration and can do things that have negative impact on him and the crowd.